"Oil above Water": Economic Interdependence and Third-party Intervention. (October 2016) - Bove, Vincenzo; Gleditsch, Kristian Skrede; Sekeris, Petros G.
We explore economic incentives for third parties to intervene in ongoing internal wars. We develop a three-party model of the decision to intervene in conflict that highlights the role of the economic benefits accruing from the intervention and the potential costs. We present novel empirical results on the role of oil in motivating third-party military intervention. We find that the likelihood of a third-party intervention increases when (a) the country at war has large reserves of oil, (b) the relative competition in the sector is limited, and (c) the potential intervener has a higher demand for oil.